Real-life experiences and barriers to adjuvant chemotherapy in Saudi patients with advanced stage II and stage III colon cancer - Mesnad S Alyabsi; Anwar H Alqarni; Adel F Almutairi; Nahar A Alselaim; Mohammed A Algarni; Kanan M Alshammari (The Saudi Journal of Gastroenterology, 2024)
Background: Colorectal cancer is the most common malignancy in Saudi males and third most common in females. Patients with locally advanced colon cancer may eventually develop metastatic disease if not treated promptly and according to guidelines. The recent National Comprehensive Cancer Network guideline recommends tumor resection followed by adjuvant chemotherapy for stage III and high-risk stage II tumors. Therefore, the objective of this study was to characterize patients with locally advanced colon cancer and identify factors associated with the use of adjuvant chemotherapy and the addition of oxaliplatin in locally advanced colon cancer patients. Methods: All patients diagnosed with locally advanced colon cancer at National Guard Health Affairs (NGHA) during 2016-2021 were investigated. Patients' characteristics were compared using Chi-square and Fisher exact test, whereas predictors of adjuvant chemotherapy/Oxaliplatin use were identified using univariate and multivariate logistic regression. Results: Out of 222 patients diagnosed with locally advanced colon cancer, 133 received adjuvant chemotherapy. Factors associated with adjuvant chemotherapy administration were age and smoking status. In the multivariable analysis, older patients were less likely to receive oxaliplatin than younger patients. Stage III patients diagnosed during 2019-2021 had 5.61 times higher odds of receiving oxaliplatin. Conclusion: The findings of this study show that older patients and smokers are less likely to be treated with adjuvant chemotherapy. Moreover, age as well as diagnosis year were important determinants of oxaliplatin administration in stage III locally advanced colon cancer patients.